Effect of CuOx additive site to graphene nanoribbon on its adsorption for hydrogen sulfide - Ahmad I. Ayesh (10188469) (2021)
A first principles investigation is carried out in this work for the adsorption of H2S gas on pristine and modified armchair-graphene nanoribbon (AGNR). CuOx (x = 0, 1, or2) is introduced to AGNR structures either by substitution of carbon atoms or through the decoration of their surfaces. The effect of modification on adsorption of H2S gas is explored using density functional theory (DFT) calculations of band structure, adsorption energy (EAds), charge transfer (ΔQ), adsorption length, and density of states (DOS). The results demonstrate great enhancement towards H2S adsorption upon modification. In general, the adsorption energy of H2S is higher for structures where CuOx substitutes carbon atoms as compared with structures where CuOx decorates AGNR surface. The results indicate that AGNR doped with CuO2 exhibits the maximum adsorption energy, followed by AGNR doped with CuO. AGNR doped with Cu or decorated with Cu, CuO, or CuO2 exhibit lower adsorption energy for H2S. Finally, the achieved results indicate that AGNR doped with CuO2 or CuO have potential for H2S sensor applications. Other Information Published in: Results in Physics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.rinp.2021.104199